Advances on statistical/thermodynamical models for unpolarized structure functions - Trevisan, Luis A.; Mirez, Carlos; Tomio, Lauro [UNESP] (AIP Publishing, 2013)
During the eights and nineties many statistical/thermodynamical models were proposed to describe the nucleons' structure functions and distribution of the quarks in the hadrons. Most of these models describe the compound quarks and gluons inside the nucleon as a Fermi / Bose gas respectively, confined in a MIT bag[1] with continuous energy levels. Another models considers discrete spectrum. Some interesting features of the nucleons are obtained by these models, like the sea asymmetries d̄/ū and d̄-ū. © 2013 American Institute of Physics.
Keywords: fermions gas; Hadron's structure functions; quarks; thermodynamical/statistical models